Intelligent disobedience : the difference between good and great leaders - McGannon, Bob, 1960- (Routledge, 2018)
Obeying all of the rules rarely generates breakthrough business performance because it does not generate new approaches. Breaking the rules randomly does not work either. Intelligent disobedience values improved business performance over compliance with the rules, when conditions permit. This is the essence of intelligent disobedience: knowing when and how to break, bend, or invent new rules to get better outcomes. This book promotes enhanced performance by promoting a higher form of ethics. Intelligent disobedience seeks to surface hidden truth and to produce actions that are of higher integrity to yield superior results. The book guides the reader to evaluate their work environment, current business results, and risk, to determine if, when, and how acting with intelligent disobedience can enhance their business outcomes and their career. Intelligent Disobedience: The Difference between Good and Great Leaders seeks to: enhance the reader's business success; help the reader examine methods for proposing potentially unpopular directions or opinions; propose a decision-making process for when the reader should "bend or break the rules"--Leveraging common sense over common processes on an exception basis; guide the reader to determine instances in which improved outcomes are better than ensuring compliance with corporate norms or management directions. This rich and sophisticated book interweaves real-life experiences from successful leaders with the themes of human psychology, ethics, decision making, delegation, communicating upwards and downwards ... Everything the senior manager needs to survive and thrive in a complex, uncertain, ambiguous, and fast-changing world